Evaluation of antioxidant properties of Mallotus oppositifolium in in-vitro, in-vivo and ex-vivo model systems (2010)
The protective effect of antioxidants and naturai !y occurring substances against oxidative stress damage has recently attracted much attention. The ieaves of Mallotus oppositifolium, a shrub of thè famìly Euphorbiacea that grows in many parts of Africa, are used in folk medicine and herbal preparations for die treatment of dysentery, worms and malaria. The study in vestigated thè antioxidant properties of thè methanolic extract of thè Ieaves of Mallotus oppositifolium (MEMO) in comparison with butylated hydroxyl anisole (BHA) as a standard antioxidant using three free radicai generators viz hydrophilic radicai generator 2,2-azobis(2- amidino propane) dihydrochloride (AAPH), hydrophobic radicai generator 2,2-azobis(2,4-dimethylvaleronitrile) (AMVN) and hydroxyl radicai and non-specific radicai generator Fe2+/ascorbate System in an in vitro, in vivo and ex-vivo model systems. Phytochemical analysis of thè Ieaves extract was al so assessed. Phytochemical analysis of thè powdered Ieaves revealed thè presence of alkaloids, tannins, cardenolides and saponins. In vitro study indicated that while MEMO failed to inhibit lipid peroxidation (LPO) induced by AAPH, while BHA offered 55.5% inhibition. In addition, while AMVN- induced LPO was inhibited by 17.7% and 29.4% by MEMO and BHArespectively, Fe2+/ascorbate system- induced LPO was inhibited by 57.9% and 78.9% by MEMO and BHArespectively. Ex-vivo studies showed that MEMO at lOOmg/kg bw reduced malondialdehyde and protein carbonyl levels by 34.5% and 12.0% respectively compared with thè control. In vivo, MEMO increased (P<0.05) superoxide dismutase and calai ase activities by 408.0% and 295.0% respectively. Taken together, this study demonstrates that MEMO exhibits antioxidant, radicai scavenging and enhancement of enzymatic antioxidant capacity and as such could intervene in toxicological processes mediated by free radicai mechanisms.